Stylistic Functions of the Conversion in the Ukrainian Periodicals of the 21st cent (Linguostylistic Studies, 2017)
The article considers the stylistic function of conversion, transitions of words from one lexico-grammatical stratum to another, on the materials of the contemporary Ukrainian periodicals. The author considers the issue of enriching vocabulary by means of inner linguistic resources, including the means of conversion. The study provides in-depth analysis of frequently used lexem transitions, found in the texts of periodicals, and the revealed multifrequency use of substantiation. The author suggests to clasify these substantives into two categories: the lexical units that name persons and those which nominate impersonal objects, including the groups of rarely used substantives. The usage frequency of the verbalized nouns in the texts of mass media and the stages of noun-verbalization process have been revealed and analyzed with an emphasis on the productive formants with an accent on the morphological features of the verb, acquired by nouns in the process of verbalization. The analysis of the stylistic language peculiarities of the publisistic style gives grounds to single out examples of the lexemes that are intrinsic for other styles. The article provides rich and vivid illustrative material to confirm the use of pro-nominalisation, adjectification, adverbialization in the texts of periodicals.
Keywords: publicistic text; conversion; substantivation; adverbialization; adjectivation; pro-officialization; verbalization